Exploring the Influence of the Nickel Oxide Species on the Kinetics of Hydrogen Electrode Reactions in Alkaline Media - Oshchepkov, Alexandr G.; Bonnefont, Antoine; Saveleva, Viktoriia A.; Papaefthimiou, Vasiliki; Zafeiratos, Spyridon; Pronkin, Sergey N.; Parmon, Valentin N.; Savinova, Elena R. (Topics in catalysis, 2016)
The influence of the oxidation of Ni electrodes on the kinetics of the hydrogen oxidation (HOR) and evolution reactions (HER) has been explored by combining an experimental cyclic voltammetry study, microkinetic modeling and X-ray photoelectron spectroscopic analysis. Almost 10 times enhancement of the activity of Ni in the HOR/HER has been observed after its oxidation under the contact with air at ambient conditions and assigned to the presence of NiO species on the surface of metallic Ni. The experimental cyclic voltammetry curves have been analyzed with the help of kinetic model in order to shed light on the mechanism of the HOR/HER for two types of Ni electrodes and its dependence on the presence of NiO on the surface of the electrode. The main features of the experimental current-potential curves can be reproduced with a kinetic model assuming that the free energy of the adsorbed hydrogen intermediate is increased and that the kinetics of the Volmer step is enhanced in the presence of nickel oxide species. The kinetic model provides evidence for the switching from the Heyrovsky–Volmer mechanism on metallic Ni to Tafel–Volmer mechanism on the activated electrode, where surface oxide species co-exist with metal Ni sites. Graphical Abstract